PEMBERDAYAAN UMKM MELALUI PEMANFAATAN E-COMMERCE DAN TEKNOLOGI TEPAT GUNA BERBASIS KEBUTUHAN LOKAL UNTUK MENINGKATKAN PEREKONOMIAN - Rika Kartika; Dini Martinda Lestari; Gito Syamil Basayev; Dedi Budiman (Yayasan Education and Social Center, 2026)
Cibuah Village has significant MSME potential; however, it still faces challenges in digital marketing and production efficiency. The bamboo handicraft MSME relies on conventional marketing methods, while the banana chips MSME faces issues related to high oil content in its products. This community service program aimed to improve the economic performance of MSMEs through the utilization of e-commerce and appropriate technology based on local needs. The method employed was Participatory Rural Appraisal (PRA), consisting of observation, problem identification, e-commerce website implementation, development of a simple oil spinner, seminars, and evaluation. The results showed a 60% increase in e-commerce product visits, a 30–35% increase in MSME income, a reduction in oil-draining time from 15 minutes to 7 minutes, improved product quality, and a 43.43% increase in participants’ understanding. The program successfully enhanced the productivity and competitiveness of MSMEs in Cibuah Village.